The Importance of Mentorship for Academic Purposes - Uwimana, Kevin; Kanzayire, Germaine; Dukundimana, Sperathe (Journal of Modern Hospitality, 2024)
Purpose: The primary aim of this study is to explore the role of mentorship in enhancing academic success among students. Specifically, it seeks to understand how structured mentorship programs contribute to academic performance, personal development, and professional readiness. The study also examines the factors that facilitate effective mentorship and the challenges faced by both mentors and mentees within academic settings. The principals already know many college students enter their advanced diploma graduate programs with little understanding of the complex landscape of higher education or how different philosophies in graduate programs drive expectations for academic excellence and ideal career pathways to acquired life skills. In fact, in the face of very articulate statements of purpose in their applications, many advanced graduate college students are initially unsure of what they will do with an advanced diploma. Methodology: This study adopts a mixed-methods approach, combining both qualitative and quantitative research designs. A survey was conducted with a target population of university students and academic staff, and in-depth interviews were held with key stakeholders, including mentors and mentees. Findings: Data were analyzed using statistical tools for quantitative data and thematic analysis for qualitative insights, ensuring a comprehensive understanding of mentorship’s impact on academic outcomes. The results revealed that students who participated in mentorship programs exhibited improved academic performance, higher levels of engagement, and greater confidence in career planning compared to their non-mentored peers. Contribution to Theory, Policy, and Practice: The study also identified key factors that influence mentorship success, such as the mentor-mentee relationship, frequency of interactions, and institutional support. However, challenges such as time constraints and lack of training for mentors were also highlighted.